Come back to me - Conner, Amanda; Palmiotti, Jimmy (Wonder Woman, 2020)
Joining Wonder Woman on her search for Steve Trevor is none other than his commanding officer and jack-of-all-trades Etta Candy! The two quickly find themselves trapped in a mysterious storm and land on a mysterious uncharted island. Is this where Steve went? If so, he may not have survived as the island is overrun with lost relics of the past, present and future all colliding at once! As if things weren't bad enough, lurking in the shadows is Wonder Woman's deadliest foe, the Cheetah!